About late asymptote of transient processes in the magnetic field of the dipole sources - Reva, N.V.; Portnov, V.S.; Blyalova, G.G.; Mausimbaeva, A.D. (KSU Publ., 2017)
The developed method solutions of the problem of late asymptote of transient processes in the magnetic field, the dipole sources are Innervate layered medium, underlain by an insulator. The method allows to determine the asymptotes of the late signals of the formation of a magnetic field as a power time series, which are present as a prominent member of a number of proportional t -4 and carrying information about the total longitudinal conductance of the section and a member of a number of proportional t -5 and contains information about capacity and conductivities of the layers. The algorithm of asymptotic solution based on the determination of the transition characteristics of the expanded core in the receiving operating information with one pole on the real axis of the complex plane and its structure is similar to the operating functions of the model a thin conductive layer, excited by the raised sources. The result is an asymptotic temporary solution to a temporary member of a number proportional t -5 to the received late asymptote depth equivalent to a conducting plane h is the important information of the parameter used in the analysis of experimental pulse field transient for three-layer sections. Analyzed the functional relationship of late asymptote parameter h with a longitudinal conductivity and thickness of layers. The analysis of the possibility of using late asymptotes to determine the total power conductive sediments overlying non-conductive base section. Data in the method of formation field. Theoretical developments are confirmed by the analysis of model.
Диполь көздерінің магнит өрісіндегі өтпелі үрдістердің кейінгі асимптотасы туралы
О поздней асимптоте переходных процессов в магнитном поле дипольных источников
Keywords: late asymptote; a magnetic field; an insulator; a dual-layer cut; functional factor; geoelectric cut